2023
DOI: 10.4097/kja.22681
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral nerve blocks for transvenous subpectoral pacemaker insertion in children: a randomized controlled study

Abstract: Background: Postoperative pain management after pacemaker insertion routinely uses either opioid agents, nonsteroid anti-inflammatory drugs, or paracetamol. There has been increased interest in opioidsparing multimodal pain management to minimize postoperative narcotic use. This study aims to assess postoperative pain control and opioid consumption provided by pectoral nerve blocks (PECs) versus standard postoperative pain control in pediatric patients after transvenous subpectoral pacemaker insertion.Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Only two patients complained of pain in the first 24 h postoperatively. These results are consistent with previous studies that reported PECS II block reduces postoperative pain scores and lower total opioid usage after CIED placement and, demonstrate that PECS II block can be used effectively in the management of postoperative analgesia after CIED insertion 29,30 . Yang et al 29 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Only two patients complained of pain in the first 24 h postoperatively. These results are consistent with previous studies that reported PECS II block reduces postoperative pain scores and lower total opioid usage after CIED placement and, demonstrate that PECS II block can be used effectively in the management of postoperative analgesia after CIED insertion 29,30 . Yang et al 29 .…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous studies that reported PECS II block reduces postoperative pain scores and lower total opioid usage after CIED placement and, demonstrate that PECS II block can be used effectively in the management of postoperative analgesia after CIED insertion. 29,30 Yang et al 29 reported that PECS II block provided a reduction in both cumulative pain and mean opioid consumption over the 24 h after CIED placement in children. Elhaddad et al 30 also reported that PECS II block not only reduces pain scores and opioid consumption but also provides a good hemodynamic profile in children underwent transvenous subpectoral pacemaker placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation